Analisa Pengaruh Event Tanggal Kembar, Promo dan Kepuasan Konsumen Terhadap Keputusan Pembelian Konsumen: Studi Kasus Generasi Z Pengguna Shopee di Jabodetabek - Yoga Abdiya Brata Rawa; Achmad Syamsul Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of twin date events, promos, and customer satisfaction on the purchasing decisions of Generation Z consumers using the Shopee e-commerce platform in the Greater Jakarta area. The phenomenon of twin date events, such as 11.11 and 12.12, which are accompanied by various promotions such as discounts, free shipping, and cashback, has become a significant marketing strategy in attracting consumer interest. This research uses a quantitative approach with a survey method through distributing questionnaires to 100 Generation Z respondents who actively shop at Shopee. Data analysis was conducted using the Partial Least Square (PLS) method through SmartPLS 4 software. The results showed that promos have a positive and significant influence on purchasing decisions, while twin date events and customer satisfaction did not show a statistically significant effect. This finding indicates that although events and satisfaction have an important role in shaping the shopping experience, the promo factor is the main driver in the purchasing decisions of Generation Z consumers. The implications of this study are expected to help e-commerce companies, especially Shopee, in designing more effective promotional strategies to attract and retain young customers in the digital era.